2019
DOI: 10.1177/0300060519882570
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and associated factors in older adults with hypertension

Abstract: Telomeres and telomerase play important roles in the occurrence and development of hypertension. This review was performed to clarify the factors that influence telomere length and telomerase activity in older patients and elucidate the association of these factors with hypertension. A PubMed search and critical review of studies assessing the risk factors underlying the association of hypertension with telomere length and telomerase activity was performed. Telomere length and telomerase activity were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Conceivably, decreased NO and/or increased ET-1 contributes to hypertension development. In accordance with the in vitro experiments and mouse studies above, several studies showed that patients with EH had shorter LTL compared with that in healthy normotensive individuals 25 , 30 - 35 . Unexpectedly, however, the direct analysis of arterial telomere length (ATL) from EH patients and normotensive individuals did not show a difference, which suggests that LTL may not necessarily reflect changes in ATL in EH patients 36 .…”
Section: Introductionsupporting
confidence: 79%
“…Conceivably, decreased NO and/or increased ET-1 contributes to hypertension development. In accordance with the in vitro experiments and mouse studies above, several studies showed that patients with EH had shorter LTL compared with that in healthy normotensive individuals 25 , 30 - 35 . Unexpectedly, however, the direct analysis of arterial telomere length (ATL) from EH patients and normotensive individuals did not show a difference, which suggests that LTL may not necessarily reflect changes in ATL in EH patients 36 .…”
Section: Introductionsupporting
confidence: 79%
“…Low telomerase activity and short LTLs were shown to be associated with atherosclerotic plaque instability and higher risk for coronary heart disease, myocardial infarction or stroke (Yeh and Wang, 2016 ; Tian et al, 2019 ; Zhan and Hägg, 2019 ). Significant associations were observed between the high rate of age-related LTL attrition and hypertension (Liu et al, 2019b ). In a systematic review comprising 119,439 individuals in total, a weak to moderate association between obesity and TL was observed in 39 of 63 included studies; a significant heterogeneity, however, was observed between studies (Mundstock et al, 2015 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…Caloric restriction and rapamycin treatment are also involved in anti-aging process, increase in lifespan, improvement of physiological functions, and reduction of pathology ( 137 ). On the other hand, a chronic inflammatory condition such as obesity is associated with decreased size of telomere length and also with increased oxidative stress in cells, leading to early aging and dementia ( 142 , 143 ). Regular physical activity can be associated with decreased levels of oxidative stress and pathological inflammation.…”
Section: Genetic and Epigenetic Factors As Major Determinants Of Immumentioning
confidence: 99%